ADAPTIVE STRATEGY OF PROSPEROUS JUSTICE PARTY: THE KEY TO VICTORY IN THE 2024 LEGISLATIVE ELECTION FOR 5 BEKASI CITY CONSTITUENCIES BASED ON PETER SCHRODER’S MODEL - Pangestu, Dernat Rasta; Rofieq, Ainur (KYBERNAN: Jurnal Ilmiah Ilmu Pemerintahan, 2025)
General elections are a cornerstone of democracy in Indonesia, providing space for public participation in determining leadership and policy direction. In the 2024 Legislative Election in Bekasi City, the Prosperous Justice Party (PKS) secured the highest number of seats in the Regional House of Representatives (DPRD), positioning itself as a key actor in the local political contest. This study aims to analyze PKS’s winning strategy in Electoral District 5 of Bekasi City (Pondok Gede and Bekasi Barat) using Peter Schroder’s political strategy model, which distinguishes between defensive strategies (maintaining the voter base) and offensive strategies (expanding voter support). The research employed a qualitative method, collecting data through in-depth interviews and observations with party cadres and community leaders. The findings reveal that defensively, PKS consolidated its loyal base through cadre networks, local leaders’ engagement, and consistent community service programs. Offensively, PKS reached out to young voters, penetrated non-loyal communities, and utilized social media as an integrated tool for political communication. The combination of these strategies proved effective in sustaining PKS’s electoral support while simultaneously expanding public sympathy, although challenges such as voter pragmatism and inter-party competition remain significant.